Requirement of mature dendritic cells for efficient activation of influenza A-specific memory CD8+ T cells. - Larsson, M; Messmer, D; Somersan, S; Fonteneau, J; Donahoe, S; Lee, M; Dunbar, P; Cerundolo, V; Julkunen, I; Nixon, D; Bhardwaj, N (2000)
It is critical to identify the developmental stage of dendritic cells (DCs) that is most efficient at inducing CD8+ T cell responses. Immature DCs can be generated from monocytes with GM-CSF and IL-4, while maturation is accomplished by the addition of stimuli such as monocyte-conditioned medium, CD40 ligand, and LPS. We evaluated the ability of human monocytes and immature and mature DCs to induce CD8+ effector responses to influenza virus Ags from resting memory cells. We studied replicating virus, nonreplicating virus, and the HLA-A*0201-restricted influenza matrix protein peptide. Sensitive and quantitative assays were used to measure influenza A-specific immune responses, including MHC class I tetramer binding assays, enzyme-linked immunospot assays for IFN-gamma production, and generation of cytotoxic T cells. Mature DCs were demonstrated to be superior to immature DC in eliciting IFN-gamma production from CD8+ effector cells. Furthermore, only mature DCs, not immature DCs, could expand and differentiate CTL precursors into cytotoxic effector cells over 7 days. An exception to this was immature DCs infected with live influenza virus, because of the virus's known maturation effect. Finally, mature DCs pulsed with matrix peptide induced CTLs from highly purified CD8+ T cells without requiring CD4+ T cell help. These differences between DC stages were independent of Ag concentrations or the number of immature DCs. In contrast to DCs, monocytes were markedly inferior or completely ineffective stimulators of T cell immunity. Our data with several qualitatively different assays of the memory CD8+ T cell response suggest that mature cells should be considered as immunotherapeutic adjuvants for Ag delivery.